Exposure to Online Da'wah Messages among Young Social Media Users in Aceh: A Reflection of Habermas's Communicative Action - Bhakti, Sufri Eka (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This study aims to reveal the transformative power of social media platforms as a new form of public sphere for religious discourse amongst Acehnese Muslim students. Using a descriptive quantitative method through online survey with 129 of those students, this study shows that social media have contributed providing a new public sphere for young Muslim and have become an essential part of Islamic proselytising (da'wah). In this regard, most young social media users utilised social media to discuss Islamic da'wah as well as to express their thought concerning on shariah enforcement. Therefore, this study argues that social media use has a close relationship with the increase of religious thoughts and knowledge as the implementation of da'wah.